Sequential injection lab-on-valve simultaneous spectrophotometric determination of trace amounts of copper and iron - Shinsuke Ohno (2018)
A sequential injection (SI) method in a lab-on-valve (LOV) format for simultaneous spectrophotometric determination of copper and iron has been devised. The detection chemistry is based on the complex formation of 2-(5-bromo-2-pyridylazo)-5-[N-n-propyl-N-(3-sulfopropyl)amino]aniline (5-Br-PSAA) with copper(II) and/or iron(II) at pH 4.6. Copper(II) reacts with 5-Br-PSAA to form the complex which has an absorption maximum at 580 nm but iron(III) does not react. In the presence of a reducing agent only iron(II)-5-Br-PSAA complex is formed and detected at 558 nm. Under the optimum experimental conditions, the determinable ranges are 0.1-2 mg l-1for copper and 0.1-5 mg l-1for iron, respectively, with a sampling rate of 18 h-1. The limits of detection are 50 μg l-1for copper and 25 μg l-1for iron. The relative standard deviations (n = 15) are 2% for 0.5 mg l-1copper and 1.8% for 0.5 mg l-1iron when determined in standard solutions. The recoveries range between 96 and 105% when determining 0.25-2 mg l-1of copper and 0.2-5 mg l-1of iron in artificial mixtures at copper/iron ratios of 1:10 to 5:1. The proposed SI-LOV method is successfully applied to the simultaneous determination of copper and iron in multi-element standard solution and in industrial wastewater samples. © 2005 Elsevier B.V. All rights reserved.